The role of firm size in moderating the relationship between earnings management and financial performance: empirical evidence from the transportation and logistics sector - Dewanti, Nyoman Dewi Ayu Ratih Arya; Sudarma, Made; ⁠Amirya, ⁠Mirna (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
This study examines the relationship between earnings management and financial performance by distinguishing between accrual earnings management and real earnings management practices. In addition, this study investigates the moderating role of firm size in influencing the relationship between earnings management and financial performance. A quantitative approach was employed using secondary data obtained from 38 companies in the transportation and logistics sector listed on the Indonesia Stock Exchange during the 2019–2024 period, resulting in 138 firm-year observations. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS software. The findings suggest that real earnings management has a positive effect on financial performance, indicating that operational adjustments may improve short-term financial outcomes. In contrast, accrual earnings management has a negative effect on financial performance, suggesting that accrual-based manipulation may reduce earnings quality and fail to reflect the firm’s actual economic condition. Furthermore, firm size does not moderate the relationship between accrual earnings management and financial performance. However, firm size strengthens the relationship between real earnings management and financial performance, indicating that larger firms have greater capacity to utilize operational strategies to influence reported performance. These findings contribute to the literature by highlighting the different implications of accrual and real earnings management for financial performance and emphasizing the contextual role of firm size. However, the results should be interpreted with caution due to the limited sample size, sector-specific focus, and the use of a single proxy for real earnings management.